Sexual behaviour, structural vulnerabilities and HIV prevalence among female sex workers in Pakistan. (14th February 2013) - Mishra, Sharmistha; Thompson, Laura H; Sonia, Altaf; Khalid, Nosheen; Emmanuel, Faran; Blanchard, James F
Abstract : Background: We sought to describe differences in individual and structural vulnerabilities faced by female sex workers (FSWs) in Pakistan between 2006 and 2011, and to characterise risk factors for inconsistent condom use and HIV prevalence in this population. Methods: To describe differences in vulnerabilities, we analysed behavioural data from serial cross-sectional surveys conducted across nine cities in 2006 and 2011. Using data from 12 cities in 2011, we used logistic regression to characterise risk factors for (a) inconsistent condom use in the past month (N=6987), and (b) HIV (N=4301). Results: Compared to FSWs in 2006, FSWs in 2011 were significantly more likely to solicit clients via cell phones, and to report a larger client volume and anal sex with clients, but also consistent condom use with clients (30.0% vs 23.6% in 2006). In 2011, independent risk factors for inconsistent condom use with clients included: recent sexual violence, recent sex with a person who injects drugs, and absence of programme exposure. HIV prevalence was 0.63% (95% CI 0.43% to 0.92%) in 2011, and was associated with a recent history of injection drug use and absence of programme exposure. Conclusions: While condom use with clients was higher in 2011, protective behaviours remained low and vulnerabilities related to sex work may have risen. HIV is emerging in this population and an adaptive HIV prevention programme that addresses different vulnerabilities and the intersection of sexual networks with injection drug use is needed.